(untitled) (Research, Society and Development, 2021)
The advancement of pharmaceutical technology demonstrated an increase in the manufacture of medicines, which has contributed to the increase in self-medication and inappropriate disposal. This study aimed to evaluate self-medication, storage and disposal of medicines in patients from private pharmacies in Jaraguá do Sul, SC. Therefore, a questionnaire was applied to customers who attend private pharmacies in the municipality. The questionnaire had 32 questions, divided into 4 stages: sociodemographic data, prevalence of self-medication and the profile of medication consumption, knowledge about the storage, validity and integrity of the drugs and knowledge about the correct disposal and the impact caused to the environment. With the results obtained from 120 patients, it was possible to observe that 91.7% of them are self-medicating. In addition, it was observed that 65% never received guidance on how to dispose of expired or out-of-use medications. For this reason, 58% of respondents discarded inappropriately, and studies show that when in contact with soil and water, these drugs can cause contamination, which even in a sewage treatment network is not completely eliminated. With the results of the present study, we concluded that the population has its share of responsibility and must also be informed and involved in the process of raising awareness of the use, storage and generation of residues derived from medicines, reinforcing the need for education strategies on the subject.